The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.14393/rbcv72nespecial50anos-56568
|View full text |Cite
|
Sign up to set email alerts
|

Estado da Arte do Sensoriamento Remoto por Radar: Fundamentos, Sensores, Processamento de Imagens e Aplicações

Abstract: Este artigo aborda o estado da arte do sensoriamento remoto por radar e foi elaborado para fazer parte da edição especial de comemoração dos 50 anos desta revista. Neste estudo, é apresentada uma breve introdução sobre os fundamentos do sensoriamento remoto por radar, com destaque para os parâmetros mais importantes de imageamento e da superfície terrestre envolvidos no processo de obtenção de imagens de radar. Ênfase é dada para o comprimento de onda, polarização das ondas eletromagnéticas e geometria de obte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Thus, models were constructed with the combination of Sentinel-1 and Sentinel-2 data through multiple linear regression (R² of 0.52 and RMSEr of 46.98%), and only Sentinel-2 data (R² of 0.63 and RMSEr of 42.03%) were superior to the models constructed using only Sentinel-1 data (R² of 0.18 and RMSEr of 59.48%). These results are similar to those found in the present study (R² of 0.1742), which corroborates the argument that the L-band has a longer wavelength that can penetrate deep into the forest, while the dominant scattering processes in the Xand C-bands (used in this study) occur at the surface of the canopy layer (Sano et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, models were constructed with the combination of Sentinel-1 and Sentinel-2 data through multiple linear regression (R² of 0.52 and RMSEr of 46.98%), and only Sentinel-2 data (R² of 0.63 and RMSEr of 42.03%) were superior to the models constructed using only Sentinel-1 data (R² of 0.18 and RMSEr of 59.48%). These results are similar to those found in the present study (R² of 0.1742), which corroborates the argument that the L-band has a longer wavelength that can penetrate deep into the forest, while the dominant scattering processes in the Xand C-bands (used in this study) occur at the surface of the canopy layer (Sano et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…The correlation for the variables arising from the Sentinel-1 image was lower, which can be explained by the characteristics of the sensor, as the backscatter is dependent on surface characteristics, bandwidth (in this case, the C-band: 3.8 cm -7.5 cm), and type of polarization (Mauya et al, 2019). This can influence the degree of signal penetration in the forest, and consequently the degree of response obtained; the longer the wavelength, the greater the penetration capacity of the signals emitted from the vegetation canopy or the ground surface (Sano et al, 2020). Another important factor is the structure of the canopy of the stand.…”
Section: Discussionmentioning
confidence: 99%
“…This denotes the complexity of soil texture for statistical modelling due to the size magnitude of the soil fractions and the mineral constitution, as well as the reliance of the signal intensity from the SAR beam on how clayey or sandy the soil is. Typically, crosspolarization (VH) measurements are significantly lower than the co-polarization (VV) (Sano et al, 2020;Ulaby et al, 1978;Ulaby et al, 1979), and this was observed over our study area wherein the VV intensity values (in σ 0 units) ranged from 0.01 to 0.31, whereas for VH polarization the coefficient backscatter varied between 0.02 and 0.07. It is worth noting that the Sentinel-1 dataset was acquired during a dry period (03/04/2021).…”
Section: General Aspects Of Soil Particle-size Estimation With Sentin...mentioning
confidence: 70%